Effect of exercise intensity on standing shooting performance and related technical variables in biathlon - Danielsen, J.; Luchsinger, H.; Wikström, A.; Laaksonen, M. S.; Sandbakk, Ø.; McGhie, D. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Biathlon is an Olympic endurance sport that combines skating style cross-country skiing (~7.5-20 km) and rifle shooting (2-4 series of 5 shots), where ~30-53% of the final performance rank is determined by shooting performance (Luchsinger, 2017). Biathletes perform shooting training both in resting conditions and at exercise intensities ranging from low to high. This study examined the effect of exercise intensity on hit percentage and related technical variables in standing shooting during roller ski skating under ecological conditions. It was hypothesized that increasing exercise intensity would impair shooting performance, with rifle barrel velocity as a significant mediator.